TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK HUTANG PIUTANG - Ilham Fadillah Fikri; Nia Kurnia; Ela Hodijah N (STAI Sebelas April Sumedang, 2024)
Debt and credit is a contract of help, additional conditions or interest at the beginning are not allowed. However, in reality, many debt and credit transactions that require excess occur in the community, this fact can be seen in Deasa Sukamantri, Tanjungkerta District, Sumedang Regency, where the majority of the population is Muslim. The factors behind this debt and credit transaction are due to urgent needs and daily necessities. Seeing this phenomenon, the author is interested in researching which refers to the following subject matter: How is the review of Islamic law on the practice of debt and credit in the community of farmers and rice dealers in Sukamantri Village, Tanjungkerta District, Sumedang Regency